Resolving alternative structure determinations of indapamide using 13C solid-state NMR. Issue 30 (28th March 2022) - Evans, Caitlin L.; Evans, Ivana Radosavlijević; Hodgkinson, Paul
Abstract : The conflict between alternative crystal structures in the Cambridge Structural Database for the diuretic drug indapamide hemihydrate has been resolved with the aid of 13 C solid-state NMR. Abstract : The conflict between alternative crystal structures in the Cambridge Structural Database for the diuretic drug indapamide hemihydrate (IND) has been resolved with the aid of 13 C solid-state NMR. IND is seen to contain multiple distinct molecules in the asymmetric unit ( Z ′ = 4) rather than exhibiting disorder in the orientation of sulfonamide groups. The NMR crystallographic approach is a more effective tool for distinguishing between alternative structures than naïve judgements of quality based on crystallographic refinement agreement factors.